Evaluasi Profil Sensori Kopi Gayo Aceh Berbagai Merek yang Dijual di Marketplace Menggunakan Metode Analisis Deskriptif Kuantitatif - Anderson, Teddy; Ari Yusasrini, Ni Luh; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 2 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i02.p07, 2023)
This study aims to identify the sensory profile of gayo aceh coffee quantitatively using the QDA method. The research phase began with panelist selection, which is followed by 15 people. The panelists who were selected and met the requirements were 10 people and proceeded to the next stage, namely FGD. The FGD stage aims to identify and determine the sensory attributes detected in coffee. Then proceed with sample preparation and testing, filling the test questionnaire and continued to the final stage of the research which is proceeding the data from the QDA analysis. The QDA result data is displayed in the form of spider web graphs and PCA biplot graphs. The results obtained 10 qualified and trained panelists who are baristas from Starbucks Tomang Raya and 13 sensory attributes identified in Gayo Aceh coffee consisting of floral aroma, fruity aroma, peanut aroma, chocolate aroma, spice aroma, bitter taste, sweet taste, sour taste, viscosity level, bitter aftertaste, dry aftertaste, astringent aftertaste and sour aftertaste. There are characteristic differences in each samples such as the "Hatana Coffee" brand sample which has dominant attribute of chocolate aroma and bitter aftertaste, the "Kafe.Inc" sample. which has the dominant attribute of sweet taste, the "Sentra Kopi" sample has the dominant attribute of peanut aroma, the "SOPIC" sample has the dominant attribute of floral aroma and bitter taste, the "Sunset Lotus" sample has the dominant attribute of fruity aroma, sour taste, and sour aftertaste, and the "Tageto Coffee" sample has the dominant attribute of spice aroma with high viscosity, dry and astringent aftertaste, while the coffee samples with the "Kieta Coffee" and "Sakha Coffee" brands tend to have chocolate and peanut aromas. This is because of the type of coffee used, the coffee roasting profile, or the post-harvest method of coffee.